Effects of potassium and magnesium on cassava vegetative and root yield - Sanginga, A.D. (University of Eldoret, 2022)
Cassava (Manihot esculentum) has a high potassium (K) demand and its application does not generally increase yields. Potassium may have antagonistic effects on magnesium (Mg) leading to deficiency of Mg in the soil. The objectives of this study were to (I) evaluate the vegetative growth of cassava under different K and Mg fertilizer combinations and (ii) determine the effects of K and Mg fertilizer on cassava storage root yield. A 2-cropping season experiment was conducted in a randomized complete block design (RCBD) to evaluate cassava variety TME419 at different combinations of K and Mg in Ibadan (7°2916N, 3.5302° E), southern Nigeria. Fertilizer treatments included 0, 90 and 180 kg ha-1 of K, 0 and 15.5 kg ha-1 of Mg and 20.5 kg ha-1 sulphur (S) to account for the S in Kieserite (MgSO4) combined as follows: control (F0), 90 K kg ha−1 (F1), 180 K kg ha−1 (F2), 0 K:15.5 Mg:20.5 S (F0+Mg1), 90 K:15.5 Mg:20.5 S kg ha−1 (F1+Mg1), 180 K:15.5 Mg:20.5 S kg ha−1 (F2+Mg1), 90 K:20.5 S kg ha−1 (F1-Mg+S) and 180 K:20.5 S kg ha−1 (F2-Mg+S). A uniform rate of 75 kg ha−1 nitrogen (N) and 20 kg ha−1 phosphorous (P) was applied to these treatments except on the control and F0+Mg1. Fertilizer treatments containing K had longer stem, fresh and dry total aboveground yield than the control and non-K treatment (F0+Mg1). Treatment F1-Mg+S had the longest stem, higher fresh and dry stem yield, while treatment F2+Mg1 outyielded other treatments on both fresh and dry leaves yield and total aboveground yield. An average of 2 stems per plant were observed on cassava grown in all fertilizer combinations. The 2 cropping seasons were significantly (p < 0.05) different for all vegetative and yield attributes, with maximum vegetative yield in the first cropping season. Although there was no significance (p > 0.05) among the fertilizer treatments for storage root yield, the interaction between K ×Mg increased the fresh storage root yield and storage root dry matter yield (DM) by 14.58% and 20.8%, respectively, upon fertilization with F2+Mg1. Further, fresh storage root yield and storage root DM yield increased by 13.23% and 14.23%, respectively, in the plots fertilized with F2. Cassava plants fertilized with F0+Mg1 recorded the highest root: shoot (R: S= 1.02) and harvest index (HI =0.90). The differences between the two cropping seasons on fresh storage root yield and root DM yield were 17.35% and 21.52%, respectively. The R:S and HI between the two cropping seasons also varied by 24.2% and 26.57%, respectively. Fresh storage root yield had significant positive correlations with the fresh total aboveground matter (r= 0.66*) in the first cropping season and (r= 0.51*) in the second cropping season. The interaction between K and Mg at the combination of 180 K:15.5 Mg:20.5 S kg ha−1 (F2+Mg1) highly enhanced the vegetative and root yield of cassava variety TME419. Therefore, the combination of 180 K:15.5 Mg:20.5 S kg ha−1 should be used by farmers to enhance cassava variety TME419 yield and balance the K and Mg fertility status of the soil.